Concentration, capital, and bank stability in emerging and developing countries - Son Tran; Dat Nguyen; Liem Nguyen (Borsa Istanbul Review, 2022)
This study uses aggregate data from 133 developing and emerging markets from 2002 to 2020 and investigates how market concentration and capital are related to bank stability. We find that banks operating in more concentrated banking markets tend to be more stable than those operating in a less concentrated market, which supports the concentration–stability hypothesis. Furthermore, the research reveals that capital significantly influences banks’ financial stability in developing and emerging markets, highlighting the role of capital as a significant financing source in these countries. Importantly, evidence shows that market concentration might enhance the positive effect of capital on bank stability. The findings should be important for policymakers, bank managers, and fund providers for banks to uphold bank stability in the less developed financial markets. These findings are robust to regression models that include alternative bank stability and market concentration proxies.